Gymnastic play as movement-based learning to enhance bodily–kinesthetic intelligence in early childhood - Nilawati Tajuddin; Silvi Indriani (CV. SPDFHarmony, 2025)
Background: Bodily–kinesthetic intelligence is an essential component of early childhood development, closely related to children’s ability to control body movements, coordinate muscles, and express ideas through physical activity. In early childhood classrooms, stimulation of bodily–kinesthetic intelligence is often limited to routine movement and song activities that do not fully engage children. Movement-based learning, particularly gymnastic play, offers structured physical experiences that integrate balance, strength, coordination, and active engagement. However, empirical evidence examining gymnastic play as a systematic learning intervention in early childhood education remains limited. Aims: This study aims to examine the effect of gymnastic play as a movement-based learning strategy on the improvement of bodily–kinesthetic intelligence in early childhood learners. Method: This study employed a quantitative quasi-experimental design using a posttest-only control group. The participants were children from Group B at TK Harniatun Arrazzaq Bandar Lampung, divided into an experimental group and a control group. The experimental group received gymnastic play activities, while the control group followed conventional movement-based instruction. Data were collected through questionnaires, observations, and documentation, and analyzed using validity and reliability testing, normality and homogeneity tests, and an independent samples t-test. Results: The results show a significant difference in bodily–kinesthetic intelligence between the experimental and control groups. Children who participated in gymnastic play activities achieved higher mean scores and demonstrated better coordination, balance, agility, and movement control compared to those in the control group. Conclusion: Gymnastic play is an effective movement-based learning approach for enhancing bodily–kinesthetic intelligence in early childhood education. Structured and engaging physical activities support children’s motor development and active participation in learning.